325 años de aporte social y humanístico de la Facultad de Ciencias Médicas, un modelo de las artes liberales - Ramírez Molina, Hernán Ramiro (2018)
Context: this article relates the 325 years of social and humanistic contribution that the Faculty of Medical Sciences (FCM) has had as a model of liberal arts.Discussion: the Central University of Ecuador (UCE) recognizes its origin, during the colony, at the Pontifical University of San Fulgencio, at the Royal and Pontifical University of San Gregorio Magno and at the University of Santo Tomás de Aquino. 325 years ago, on April 13, 1693, by Royal Decree of King Carlos II of Spain, the Faculty of Medicine was founded at the Royal University of Santo Tomás de Aquino, which through an Organic Decree of Public Education dictated by President Vicente Rocafuerte, of December 20, 1836 provides "The University of Quito is the Central University of the Republic of Ecuador." Since then, the UCE and its FCM have maintained a progressive and sustained growth. In order to achieve this, they had to save a number of difficulties that, more than once, threatened their existence, as follows: chronic shortage of economic resources; lack of infrastructure and teaching staff; political and clerical interference; dark interests that wanted to silence her with frequent and long closures. The FCM of the UCE has managed to overcome all obstacles and obstacles Conclusion: currently the FCM is the national reference in medical education, capable of facing any challenge that modern science and society demand